Subjektivitas Ideologi Al-Suyūṭī dalam Tafsir al-Durr al-Manṡūr fī al-Tafsīr bi al-Ma’tsūr - Nada Rahmatina; Nadhiraturrahmi Aidina; Rijal Ali (IAIN Madura, 2024)
As something that is inseparable from a mufasir, a mufasir's ideological, scientific tendencies and environmental influences shape his subjectivity in interpreting the Qur'an. The interpreter's subjectivity sometimes clashes with information from hadith narratives. The clash between mufasir subjectivity and narrative objectivity is the background for this research. To achieve the research objectives, this article uses a type of literature research with qualitative research methods. The book of al-Durr al-Manṡūr fī al-Tafsīr bi al-Ma'ṡūr by Jalāl al-Dīn al-Suyūṭī is used as an object of research as well as a primary source. This article focuses on the interpretation of mutasyābih verses in the book of al-Durr al-Manṡūr, especially the nature or tajsīm verses. The tajsīm verses studied contain the terms istawā, wajhun, 'ainun, yadun, and yamīn. The results of the research are the dominance of the tawaqquf attitude by al-Suyūṭī and his tendency to follow the Salaf 'ulama who do not interpret mutasyābih verses. A different attitude was shown by al-Suyūṭī in his other works when discussing the same verse, namely in Tafsīr Jalālain and al-Itqān fī 'Ulūm al-Qur'ān. This difference in attitude is caused by the limitations of the narratives in the book al-Durr al-Manṡūr. This shows that in the interpretation of tajsim verses, when confronted with hadith narratives, al-Suyūṭī prefers a tawaqquf attitude.